GuidedMix-Net: Semi-supervised Semantic Segmentation by Using Labeled Images as Reference - Tu, Peng; Huang, Yawen; Zheng, Feng; He, Zhenyu; Cao, Liujuan; Shao, Ling (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
Semi-supervised learning is a challenging problem which aims to construct a model by learning from limited labeled examples.Numerous methods for this task focus on utilizing the predictions of unlabeled instances consistency alone to regularize networks.However, treating labeled and unlabeled data separately often leads to the discarding of mass prior knowledge learned from the labeled examples. In this paper, we propose a novel method for semi-supervised semantic segmentation named GuidedMix-Net, by leveraging labeled information to guide the learning of unlabeled instances.Specifically, GuidedMix-Net employs three operations: 1) interpolation of similar labeled-unlabeled image pairs; 2) transfer of mutual information; 3) generalization of pseudo masks.It enables segmentation models can learning the higher-quality pseudo masks of unlabeled data by transfer the knowledge from labeled samples to unlabeled data.Along with supervised learning for labeled data, the prediction of unlabeled data is jointly learned with the generated pseudo masks from the mixed data. Extensive experiments on PASCAL VOC 2012, and Cityscapes demonstrate the effectiveness of our GuidedMix-Net, which achieves competitive segmentation accuracy and significantly improves the mIoU over 7$%$ compared to previous approaches.